High expression of topoisomerase-II predicts favorable clinical outcomes in patients with relapsed small cell lung cancers receiving amrubicin. (January 2018) - Miura, Yosuke; Kaira, Kyoichi; Sakurai, Reiko; Sunaga, Noriaki; Saito, Ryusei; Hisada, Takeshi; Yamada, Masanobu
Highlights: We examined clinical outcomes in relapsed SCLC patients who received amrubicin. Higher Topo-II expression correlated closely with refractory relapse in patients. Topo-II overexpression was an independent prognostic factor for better outcomes. Topo-II expression may be a potent indicator of the efficacy of amrubicin therapy. Abstract: Objectives: Amrubicin monotherapy is a treatment option for patients with relapsed small cell lung cancers (SCLCs). Topoisomerase-II (Topo-II) – a target of amrubicin – has been reported as a predictive or prognostic marker for chemosensitivity or outcomes in patients with various malignancies. Here, we investigated the prognostic role of Topo-II expression in patients with relapsed SCLCs who underwent amrubicin monotherapy. Materials and methods: Eighty-three patients with relapsed SCLCs who received amrubicin monotherapy between 2004 and 2015, after progression beyond first-line chemotherapy, were enrolled in the study. We retrospectively collected clinical data from their medical records, and evaluated the expression levels of Topo-II, by immunohistochemical staining of archival tumor specimens obtained through surgical resections or biopsies. Results: Most of the enrolled patients were elderly men (89%), with a median age of 70 years (range, 49–83); 16% of these patients showed Topo-II overexpression. Compared to patients with sensitive relapses, those with refractory relapses showed significantly higher Topo-II expression levels ( P  = 0.03). The overall response rates in patients with high and low Topo-II expression were 38.5% and 25.7%, respectively ( P  = 0.34). Multivariate analysis confirmed that patients with a higher Topo-II expression level had significantly longer progression-free survival (hazard ratio (HR), 0.39; P  < 0.01) and overall survival (HR, 0.48; P  = 0.04), compared to patients with a lower Topo-II expression level. Conclusion: Our study identified Topo-II expression as a significant biomarker for the prediction of favorable outcomes in patients with relapsed SCLCs who underwent treatment with amrubicin, a Topo-II inhibitor. Thus, Topo-II expression may be a promising predictor of the efficacy of amrubicin.